Pengaruh Supervisi Akademik Kepala Sekolah dan Motivasi Kerja Terhadap Profesionalisme Guru Sekolah Dasar Negeri di Kecamatan Pringsurat Kabupaten Temanggung - Untoro, Joko; Nurkolis, Nurkolis; Sudana, I Made (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
Teacher professionalism can be seen from the way the teacher manages the learning process from the planning, implementation and evaluation stages of learning. The aim of this research is to: 1) determine the magnitude of the influence of academic supervision on teacher professionalism, 2) determine the magnitude of the influence of teacher work motivation on teacher professionalism, and 3) determine the magnitude of the influence of academic supervision and teacher work motivation together on teacher professionalism. The research approach used is quantitative. This type of research uses associative research. The population of this study was 230 teachers and the research sample was 146 teachers. Data collection was carried out using a questionnaire. The data analysis technique used in this research is descriptive data analysis, prerequisite tests which include normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests and hypothesis tests including simple and multiple linear regression. The research results show that: (1) the correlation between academic supervision and teacher professionalism is 0.876. The influence of academic supervision on teacher professionalism is 76.8%, (2) The correlation between teacher work motivation and teacher professionalism is 0.956. The influence of teacher work motivation on teacher professionalism is 92.1%, (3) The correlation between academic supervision and teacher work motivation on teacher professionalism is 0.960. The influence of academic supervision and teacher work motivation on teacher professionalism is 0.921 or 92.1%. The conclusions of this research are 1) the influence of academic supervision on teacher professionalism is 76.8%. 2) the influence of teacher work motivation on teacher professionalism is 92.1%. 3) the influence of academic supervision and teacher work motivation on teacher professionalism is 92.1%. The author suggests that school principals provide guidance and direction to teachers, especially so that they can improve and develop learning, then teachers can also take part in training and seminars in order to increase competence, which in turn can increase teacher professionalism.